The ionic composition of the local absorber towards 3C 273. Issue 4 (21st January 2020) - Gissis, Itay; Peretz, Uria; Behar, Ehud
ABSTRACT: Hot ionized gas is observed in the local vicinity of our galaxy through spectral absorption features. The most common hypothesis is that this gas forms a halo surrounding our Milky Way, in collisional ionization equilibrium. In this paper, we investigate the elemental abundance of this hot and ionized local gas. We use a 2.4 Ms stacked X-ray spectrum of the bright blazar 3C 273 and probe the local absorption features. Using ion-by-ion fitting of the X-ray absorption lines, we derive the column density of each ionization species. Based on the column densities, we reconstruct the absorption measure distribution, namely the hydrogenic column density as a function of temperature. We report the elemental abundances of C, N, Ne, and Fe relative to solar O. Previous measurements of local X-ray emission lines in conjunction with the present column densities indicate a scale height of 1–80 kpc and hydrogen number density of 10 −4 –10 −3  cm −3 for the hot ionized gas. Additionally, we detect He-like O lines from the quasar broad line region with velocities of 6400 ± 1500 km s −1 .